1, 4‐Diphosphinines from Imidazole‐2‐thiones. Issue 31 (28th June 2017) - Koner, Abhishek; Pfeifer, Gregor; Kelemen, Zsolt; Schnakenburg, Gregor; Nyulászi, László; Sasamori, Takahiro; Streubel, Rainer
Abstract: 1, 4‐Diphosphinines that are fused to two thiourea units were synthesized from the corresponding tricyclic 1, 4‐dichloro‐1, 4‐dihydro‐1, 4‐diphosphinines, and their structures and spectroscopic features are described. Electrochemical studies revealed very low oxidation potentials, which are due to the effective π‐interaction between the 1, 4‐diphosphinine ring and the orbitals of the two ylidic C=S bonds. In accordance with the low‐lying LUMO, which is largely localized at the two phosphorus centers, dianion formation is strongly preferred. Despite the small HOMO–LUMO gap, which is in accordance with the red color of the title compounds, theoretical calculations suggest considerable aromaticity for the 1, 4‐diphosphinine ring. Abstract : Tricyclic 1, 4‐diphosphinines (II ), with two fused thiourea units, have been synthesized from the corresponding 1, 4‐dichloro‐1, 4‐dihydro‐1, 4‐diphosphinines (I ). Their structures and spectroscopic features were studied, and the electrochemical properties suggest that their very low oxidation potentials are due to cyclic π‐conjugation. The spectroscopic properties and theoretical calculations indicate considerable aromaticity.